First person - Nagisa Yoshida (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Nagisa Yoshida is first author on 'The zebrafish as a novel model for the in vivo study of Toxoplasma gondii replication and interaction with macrophages', published in DMM. Nagisa conducted the research described in this article while a PhD student in Prof. Serge Mostowy and Dr Eva Frickel's labs at Imperial College London/The Francis Crick Institute/London School of Hygiene and Tropical Medicine, London, UK. She is now a postdoc in the lab of Dr Robindra Basu-Roy and Prof. Serge Mostowy at London School of Hygiene and Tropical Medicine, and her research interests include infection biology and immunology.